Finance and Accounting for Business - Ryan, Bob, 1947-; Ryan, Bob, 1947- (London : Soth-Western/Cengage Learning, 2008)
For every practical finance problem, from estimating a company's cost of capital through to the valuation of its tangible assets, this book places emphasis on how the job can be done using readily available tools and freely available data.
Previous ed.: published as Corporate finance and valuation. London: Thomson, 2007.
Formerly CIP.
Includes bibliographical references and index.
Keywords: Corporations -- Finance; Corporations -- Valuation